2020
DOI: 10.1017/s1368980019003379
|View full text |Cite
|
Sign up to set email alerts
|

A cross-sectional study to determine the energy density and nutritional quality of primary-school children’s lunchboxes

Abstract: Objective:The present study describes the energy content of primary-school children’s lunchboxes and the proportion of lunchbox foods considered discretionary. Subgroup analyses by sex, socio-economic status, age and weight status were undertaken.Design:A cross-sectional study was conducted. Mean kilojoule content, number of items and categorisation of foods and drinks in lunchboxes as ‘everyday’ (healthy) or discretionary (sometimes) foods were assessed via a valid and reliable lunchbox observational audit.Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 16 publications
3
20
0
Order By: Relevance
“…Foods packed within school lunchboxes may contribute to energy imbalance [77]. In this context, Qatar Academy has implemented a policy that forbids lunchboxes, except for medical reasons.…”
Section: Schoolsmentioning
confidence: 99%
“…Foods packed within school lunchboxes may contribute to energy imbalance [77]. In this context, Qatar Academy has implemented a policy that forbids lunchboxes, except for medical reasons.…”
Section: Schoolsmentioning
confidence: 99%
“…Schools are a key health promotion setting to improve children's health, including diet and activity patterns [4]. Despite this focus on schools as a setting to improve children's nutrition, in Australia children's intakes within school hours are not aligned with dietary guideline recommendations [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Analyses of primary-aged children's school food intake from the National Nutrition Survey in 1995 identified low vegetable intake and an overrepresentation of energy-dense, nutrient-poor foods in the school setting [7]. While not a nationally representative sample, a study of children's lunchbox contents in 2017 found that energy-dense, nutrient-poor foods contributed 39% of total energy packed, with 63% of children having two or more servings of these foods in their lunchbox, and only 20% of lunchboxes containing vegetables [5]. Evidence of differences in children's lunch quality as determined by socio-economic position are mixed [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…exceeding Australian dietary recommendations for primary school-aged children (12) , and over 2800 kJ (13) , equivalent to 40 % of a primary school-aged child's entire daily energy intake (14) . As such, strategies that are successful in achieving even modest improvements in the nutritional quality of foods packed in school lunchboxes could make an important contribution to improving child nutrition (15) .…”
mentioning
confidence: 99%